1978
DOI: 10.1071/bi9780267
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin Levels and Ovarian Development in the Neonatal Ewe Lamb

Abstract: Ovarian weight has been shown to increase markedly in the newborn ewe lamb, and factors which might contribute to this growth were examined. Follicle development was studied in the ovaries of 28 lambs aged 0, 2, 4, 6, 8 and 10 weeks. Plasma samples, pituitaries and one ovary were assayed for gonadotrophin or steroid hormone content.No significant differences between age groups were found in pituitary LH concentration or mean plasma LH. Pituitary FSH concentration increased with age, except for a small decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…It is not clear what triggers the development-no significant changes in circulating gonadotrophin levels have been detected in our animals (Tassell et al 1978), although Foster et al (1972) reported elevations of luteinizing hormone in the post-natal period. It has been claimed that early follicular growth is independent of gonadotrophic stimulation (Peters et al 1973).…”
Section: Introductionmentioning
confidence: 46%
“…It is not clear what triggers the development-no significant changes in circulating gonadotrophin levels have been detected in our animals (Tassell et al 1978), although Foster et al (1972) reported elevations of luteinizing hormone in the post-natal period. It has been claimed that early follicular growth is independent of gonadotrophic stimulation (Peters et al 1973).…”
Section: Introductionmentioning
confidence: 46%
“…Tassell et al Follicles were classified as described by Trounson et al (1974) and Tassell et al (1978). Primordial, small and large growing (non-vesicular), and partially and fully formed vesicular follicles were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments with ovariectomized ewe lambs established that the ovary also influences uterine growth and endometrial gland morphogenesis after PND 14 (Carpenter et al 2003a). The neonatal ovine ovary contains both the preantral and antral ovarian follicles at birth, which decline on PND 14, increase to maximum numbers on PND 28, remain high from PNDs 42 to 56, and decline thereafter (Kennedy et al 1974, Tassell et al 1978. These changes in the ovarian follicular dynamics are temporally correlated with the ontogeny of endometrial gland development in the neonatal ewe (Wiley et al 1987, Taylor et al 2001.…”
Section: Introductionmentioning
confidence: 88%